Real-Time Intraoperative Consultation Reporting in the Electronic Health Record: An Innovative Method to Enhance Communication and Promote Patient Safety. Issue 3 (11th June 2020) - Klein, Molly E; Rudolf, Joseph W; Tarbunova, Maryna; Jorden, Tanya; Clark, Susanna R; Khalifa, Mahmoud A
Abstract: Objectives: We sought to make pathologists' intraoperative consultation (IOC) results immediately available to the surgical team, other clinicians, and laboratory medicine colleagues to improve communication and decrease postanalytic errors. Methods: We created an IOC report in our stand-alone laboratory information system that could be signed out prior to, and independent of, the final report, and transfer immediately to the electronic health record (EHR) as a preliminary diagnosis. We evaluated two metrics: preliminary (IOC) result review in the EHR by clinicians and postanalytic errors. Results: We assessed 2, 886 IOC orders from the first 22 months after implementation. Clinicians reviewed 1, 956 (68%) of the IOC results while in preliminary status, including 1, 399 (48%) within the first 24 hours. We evaluated 150 cases preimplementation and 300 cases postimplementation for discrepancies between the pathologist's IOC result and the IOC result recorded by the surgeon in the operative note. Discrepancies dropped from 12 of 150 preimplementation to 6 of 150 and 7 of 150 in postimplementation years 1 and 2. One of the 25 discrepancies had a major clinical impact. Conclusions: Real-time reporting of IOC results to the EHR reliably transmits results immediately to clinical teams. This strategy reduces but does not eliminate postanalytic interpretive errors by clinical teams.